SUFISM AND TEACHER IN THE PERSPECTIVE OF SULUK THE PEACE OF LIFE SUNAN BONANG (International Conference on Social and Islamic Studies, 2021)
In the book Al arba'in fi ushul al din it is said that perfect happiness is happiness that includes two dimensions, namely the world dimension and the hereafter dimension. Happiness in the world can be felt with a peaceful soul. Happiness in the afterlife is the happiness of meeting and communicating with Allah (Ahmad Faizur Rosyad, Pole: 2004) (Zaairul, 73). In Man's search for Meaning, Dr. Viktor E. Frankl, professor of psychiatry at the University of Vienna wrote, “Man's search for meaning in life is themain force in his life and is not a secondary rationalization of instinctual movement” (J. Maurus, Cinta Pena : 2005). Achieving happiness and peace of mind is actually not as simple as we think. Why is that? Because to achieve it requires a series of efforts that always consider the needs, risks, and the sense of value created. Even the natural potential that we have, such as our psyche and our organs, is also taken into consideration (Zairul, 74).